Molecular Detection and Quantification of Pythium Species Evolving Taxonomy, New Tools, and Challenges - Schroeder, Kurtis L (Plant disease, 2013)
The genus Pythium is one of the most important groups of soilborne plant pathogens, present in almost every agricultural soil and attacking the roots of thousands of hosts, reducing crop yield and quality. Most species are generalists, necrotrophic pathogens that infect young juvenile tissue. In fact, Cook and Veseth have called Pythium the "common cold" of wheat, because of its chronic nature and ubiquitous distribution. Where Pythium spp. are the cause of seedling damping-off or emergence reduction, the causal agent can easily be identified based on symptoms and culturing. In more mature plants, however, infection by Pythium spp. is more difficult to diagnose, because of the nonspecific symptoms that could have abiotic causes such as nutrient deficiencies or be due to other root rotting pathogens. Molecular methods that can accurately identify and quantify this important group are needed for disease diagnosis and management recommendations and to better understand the epidemiology and ecology of this important group. The purpose of this article is to outline the current state-of-the-art in the detection and quantification of this important genus. In addition, we will introduce the reader to new changes in the taxonomy of this group